Prediction and verification for the models of temperature rising by medium bubbles in hydraulic system. (March 2022) - ShengQing, Yang; Hong, Ji; SenLin, Li; Fei, Sun; SuYan, Wang
In order to obtain the influence of the medium bubble contents on temperature rising characteristics of a hydraulic system, the working hydraulic system of a wheel loader was taken as the research object. By carrying out the comparison experiments of the hydraulic system with and without de-aeration devices on a 5-ton wheel loader, the air bubble contents and concerning temperatures were obtained. To identify the factors which have impact on temperature rising of the hydraulic system, the head chamber of boom cylinder is taken to analyze, and the temperature rising expression in a volume were deduced. By the utilization of the thermal hydraulic library, combining with mechanism and control libraries on AMESim simulation platform, the integrated simulation model of the whole system was established and verified, meanwhile, the simulation was carried out from aspects in different air contents and initial chamber temperatures. From the simulation, the prediction models of the air contents to temperature rising, and the pressures to temperature rising were predicted. Finally, the correctness of the prediction models are verified by experiment data and showing good results, which can be used to enrich and improve the calculation and evaluation methods of heat generation to any other hydraulic systems.